MEASUREMENT ON THE MODULE OF THE THYRISTOR IN MICROLABORATORY RC2000 - Ladislav, RUDOLF (Trends in education, 2009)
The paper is about a practical measurement on the module of the thyristor using microlaboratory rc2000. At the thyristor the system enables to model switched on states in various times. These states are evaluated by graphic outputs on the screen. Switched on states can be modelled for various times of switching. Students can better understand the function of the thyristor and its connection in practical exercises.
Keywords: Thyristor; measurement; modelling; electro-construction set; function; graphic output.